RESULTS OF TREATMENT OF CERVICAL DISCOPATHY WITH PEEK INTERBODY CAGES AT THREE LEVELS WITHOUT PLATE FIXATION - González Moga,Amado (2016)
ABSTRACT Objective: To present the results of treatment of patients with cervical discopathy by anterior cervical approach, discectomy and placement of a PEEK interbody cage without anterior plate fixation. Methods: Retrospective, cross-sectional study from March 2013 to March 2015. Sixteen patients with radiculopathy or clinical signs of myelopathy were included; all patients underwent cervical surgery through anterior approach, discectomy, and placement of PEEK cages on three levels. Decompression levels were determined according to the correlation between preoperative radiological and clinical findings. Results: Sixteen patients predominantly male were included, with mean age of 50 years at the onset of the condition. Ten patients had involvement of C4-C5, C5-C6, C6-C7 levels, and six patients C3-C4, C4-C5 and C5-C6. Fourteen patients had cervicobrachialgia and two myelopathy. The preoperative visual analog scale average was 8/10 and the average postoperative value at 6 months was 3/10. At 6 months, there was no radiological evidence of recurrence. One patient had non-fatal complications. Conclusions: The treatment of cervical discopathy by anterior approach with interbody fusion with PEEK cage on three levels, with no plate fixation seemed to be safe and effective with better long-term results in terms of pain and myelopathy. The clinical results compare favorably with other similar series and, most importantly, the complications associated with anterior fixation plate are avoided.